Problematika Frasa Tanpa Persetujuan Korban Dalam Peraturan Menteri Pendidikan Kebudayaan Riset Dan Teknologi Nomor 30 Tahun 2021 Tentang Pencegahan Dan Penanggulangan Kekerasan Seksual Di Perguruan Tinggi - Nur Anisah, Laili (Diktum: Jurnal Ilmu Hukum, 2022)
The Ministry of Education and Culture in an effort to prevent and overcome sexual violence The Ministry of Education and Culture issued Regulation No. 30 of 2021 concerning the Prevention and Control of Sexual Violence in Higher Education. The Permendikbudristek is intended as a legal basis for the processing of cases of sexual violence that occur in the Higher Education environment. However, there were several problematic substances after the Permendikbudristek was ratified, one of which was the phrase "Without Victim's Consent" which triggered the assumption that the Permendikbudristek encouraged the occurrence of free sex in universities. This study will examine the legal politics of this phrase and its implications for handling cases of sexual violence from a victim perspective. This research is a normative legal research. The results of this study, namely, the phrase "Without the Victim's Consent" cannot be interpreted as an argumentum a contrario to encourage free sex in universities. . This phrase must be proven not only to protect the victim, but also to protect the perpetrator, although it is rare. The conclusion of this study is that the phrase "Without the Victim's Consent" cannot be interpreted grammatically as opposed to the text in question, giving rise to an interpretation that not only harms the victim, but also contains accusations against higher education institutions. The phrase “Without the Victim's Consent” is needed to guarantee the rights of the victim as well as to provide legal certainty for alleged perpetrators of sexual violence in universities.